Constitutions, citizenship and indigenous people in the Andes during the XIX century: the cases of Bolivia, Ecuador and Peru - Del Águila, Alicia (2014)
This article presents a comparative analysis of the development of the citizenship and theright to vote concepts during the XIX century, in Andean countries’ constitutions, specifically in Bolivia, Ecuador and Peru. In a particular way, the question about the inclusion of the indigenous people in Peru and Bolivia was medullary in the constituent discussions, and was resolved in many ways in both countries: in Bolivia, the debate fluctuated around many solutions until the imposition of the decree for the restriction of the right to vote just for literate people on the decade of 1840 (excluding the big indigenous majority), while in Peru, that restriction would not have been implemented until 1896.Debate processes and redefinitions have not existes in Ecuador: since the first constitution, it was established the requirement of knowing read and write to exercise citizenship. The differences between Ecuador and the other two cases is related with socioeconomic and political processes, specifically the regional conflicts that difficult the consolidation of a national unity, and the relation between indigenous and plantations since the beginning of the XIX century in Ecuador. More precisely, this article tries to situate the constitutional and legislative solutions in more wide political debates, as well as the social and economic changes that they have been generating.